Le français au Portugal - José Domingues de Almeida (Carnets)
We will propose a generic and systematic balance sheet - retrospective, prospective and perspective in the changes in perception, prestige and challenges of teaching and learning of the French language in Portugal; a language that has, in the past, never really been “foreign” and that cannot find yet a normal status in the Portuguese linguistic offer and context